Unprecedented Diversity of Unique CRISPR-Cas-Related Systems and Cas1 Homologs in Asgard Archaea - Makarova, Kira S. (CRISPR J, 2020)
The principal function of archaeal and bacterial CRISPR-Cas systems is antivirus adaptive immunity. However, recent genome analyses identified a variety of derived CRISPR-Cas variants at least some of which appear to perform different functions. Here, we describe a unique repertoire of CRISPR-Cas-related systems that we discovered by searching archaeal metagenome-assemble genomes of the Asgard superphylum. Several of these variants contain extremely diverged homologs of Cas1, the integrase involved in CRISPR adaptation as well as casposon transposition. Strikingly, the diversity of Cas1 in Asgard archaea alone is greater than that detected so far among the rest of archaea and bacteria. The Asgard CRISPR-Cas derivatives also encode distinct forms of Cas4, Cas5, and Cas7 proteins, and/or additional nucleases. Some of these systems are predicted to perform defense functions, but possibly not programmable ones, whereas others are likely to represent previously unknown mobile genetic elements.